Azimuthal Anisotropy of Heavy-Flavor Decay Electrons in p -Pb Collisions at √ˢɴɴ =5.02 TeV - Acharya, S.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; Al-Turany, M.; et al. (American Physical Society, 2019)
Angular correlations between heavy-flavor decay electrons and charged particles at midrapidity (|η| <0.8) are measured in p-Pb collisions at √ˢɴɴ = 5.02 TeV. The analysis is carried out for the 0% - 20% (high) and 60% - 100% (low) multiplicity ranges. The jet contribution in the correlation distribution from high-multiplicity events is removed by subtracting the distribution from low-multiplicity events. An azimuthal modulation remains after removing the jet contribution, similar to previous observations in two-particle angular correlation measurements for light-flavor hadrons. A Fourier decomposition of the modulation results in a positive second-order coefficient (v2) for heavy-flavor decay electrons in the transverse momentum interval 1.5 < Pᴛ <4 GeV=c in high-multiplicity events, with a significance larger than 5σ. The results are compared with those of charged particles at midrapidity and those of inclusive muons at forward rapidity. The v₂ measurement of open heavy-flavor particles at midrapidity in small collision systems could provide crucial information to help interpret the anisotropies observed in such systems.
Keywords: Physics; Anisotropy; Electron; Nuclear physics; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.00